2018
DOI: 10.3892/ol.2018.9335
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑217 functions as a tumor suppressor in cervical cancer cells through targeting Rho‑associated protein kinase 1

Abstract: The abnormal expression of microRNAs (miRNAs/miRs) has been widely reported in various tumor types. miR-217 was demonstrated to be aberrantly expressed in a number of tumors, including pancreatic adenocarcinoma and osteosarcoma; however, its specific expression pattern has never been investigated in cervical cancer cells. Compared with normal control, the level of Rho-associated protein kinase 1 (ROCK1) expression was markedly increased in cervical cancer tissues and cells compared with that in non-cancerous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Therefore, the ability of miR-217 to suppress cervical cancer may be modulated through ROCK1. This was further supported by suppressed luciferase activity of pmirGLO-ROCK1-3'UTR-1 and pmirGLO-ROCK1-3'UTR-2 following overexpression of miR-217 (123). Lastly, western blot analysis revealed that overexpression of miR-217 significantly lowered ROCK1 expression levels, whereas reduced levels of miR-217 expression resulted in increased ROCK1 expression levels (Fig.…”
Section: Cancer Type Tlrsmentioning
confidence: 60%
See 4 more Smart Citations
“…Therefore, the ability of miR-217 to suppress cervical cancer may be modulated through ROCK1. This was further supported by suppressed luciferase activity of pmirGLO-ROCK1-3'UTR-1 and pmirGLO-ROCK1-3'UTR-2 following overexpression of miR-217 (123). Lastly, western blot analysis revealed that overexpression of miR-217 significantly lowered ROCK1 expression levels, whereas reduced levels of miR-217 expression resulted in increased ROCK1 expression levels (Fig.…”
Section: Cancer Type Tlrsmentioning
confidence: 60%
“…Expression of miR-217 in cervical cancer. Previous studies have revealed that miRNAs act as tumour suppressors in (123). Therefore, the ability of miR-217 to suppress cervical cancer may be modulated through ROCK1.…”
Section: Cancer Type Tlrsmentioning
confidence: 99%
See 3 more Smart Citations